2019
DOI: 10.3389/fonc.2019.00879
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Programmed Death-Ligand 1 in a Chinese Cohort With Clear Cell Renal Cell Carcinoma

Abstract: Objective: To investigate the association between tumor PD-L1 expression and patient survival to determine whether PD-L1 represents an independent prognostic feature for patients with non-metastatic clear cell renal cell carcinoma (RCC).Patients and Methods: The tissue bank of the Fudan University Shanghai Cancer Center was queried to identity tissue samples of patients treated with radical nephrectomy, for non-metastatic sporadic clear cell RCC (ccRCC) between 2008 and 2015. Real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Some studies could support our findings, for instance, Xiao and colleagues assessed the expression levels of mRNA and protein of PD-L1 in 330 patients with non-metastatic clear cell renal cell carcinoma via qRT-PCR and IHC test, respectively, and 292 patients had consistent results for mRNA and the PD-L1 protein ( 26 ), indicating that the evaluation of PD-L1 expression based on qRT-PCR technology is predictive valuable. Another study showed that, depending on the 28-8 antibody employed, the agreement between PD-L1 mRNA and IHC staining in primary non-small cell lung cancer tissues was excellent, and the differences became apparent in metastatic lesions ( 27 ).…”
Section: Discussionsupporting
confidence: 70%
“…Some studies could support our findings, for instance, Xiao and colleagues assessed the expression levels of mRNA and protein of PD-L1 in 330 patients with non-metastatic clear cell renal cell carcinoma via qRT-PCR and IHC test, respectively, and 292 patients had consistent results for mRNA and the PD-L1 protein ( 26 ), indicating that the evaluation of PD-L1 expression based on qRT-PCR technology is predictive valuable. Another study showed that, depending on the 28-8 antibody employed, the agreement between PD-L1 mRNA and IHC staining in primary non-small cell lung cancer tissues was excellent, and the differences became apparent in metastatic lesions ( 27 ).…”
Section: Discussionsupporting
confidence: 70%
“…Clear cell RCC is the most common RCC subtype and has already been extensively analyzed for PD-L1 expression in earlier studies [ 14 , 18 21 , 25 , 26 , 28 , 29 , 31 , 32 , 35 , 39 , 40 , 49 , 51 ]. Our rate of 2–6% PD-L1 positive clear cell RCCs (depending on the cut-off level to define PD-L1 positivity) is in the lower range of published data with PD-L1 positivity ranging from 0 to 77% in studies analyzing 34–756 clear cell RCCs [ 14 , 18 21 , 25 , 26 , 28 , 29 , 31 , 32 , 35 , 39 , 40 , 49 , 51 ]. Reasons that are typically hold accountable for discrepant results in IHC studies include different antibodies, staining protocols, and criteria to define positivity.…”
Section: Discussionmentioning
confidence: 99%
“…The H-score was determined by the following calculation method: H-score = % of weakly stained cells (1+) + 2 × % of moderately stained cells (2+) + 3 × % of strongly stained cells (3+). Positive CD47 expression was defined as H-score ≥ 5 (≥5% tumor cell membrane staining) according to reference studies [ 26 , 27 ]. All immunohistochemical assessments were blinded to the clinicopathological parameters and patient survival.…”
Section: Methodsmentioning
confidence: 99%